Biological control of the bronze bug, Thaumastocoris peregrinus, in eucalyptus plantations in Brazil - Wilcken, Carlos Frederico [UNESP]; Barbosa, Leonardo Rodrigues; Zache, Bruno [UNESP]; Firmino, Ana Carolina [UNESP]; Sá, Luiz Alexandre Nogueira de; Zanuncio, Jose Cola; Junqueira, Luis Renato (My University, 2014)
The bronze bug Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) was detected in Brazil in 2008 and infested >180 000 ha of eucalyptus plantations in 2011. The bronze bug can cause a reduction of 10–15% in wood productivity after 2 years of heavy infestation. Although there is not an effective control method known, biological control is the main control strategy studied. An exotic egg parasitoid, Cleruchoides noackae (Hymenoptera: Mymaridae), was imported from Australia in 2012, reared in a laboratory and released in three Brazilian regions. Parasitoids were recovered at release points after 20–30 d. In 2013, preliminary evaluations demonstrated parasitoid establishment in these areas, and the parasitoid was recovered in adjacent areas after 1 year of release. Bioassays confi rmed egg parasitism of 15–20% by C. noackae. Other native natural enemies were studied. We found green lacewing Chrysoperla externa and predatory bugs Supputius cincticeps and Atopozelus opsimus preying on nymphs and/or adults of T. peregrinus. Another promising possibility is entomopathogenic fungi. Commercial formulations of Beauveria bassiana were tested with success in lab and fi eld conditions. Fusarium proliferatum and Paecilomyces cateniannulatus caused mortality of T. peregrinus in natural epizooties. After 5 years of research, it is possible to develop an integrated pest management system (IPM) for eucalyptus plantations based on biocontrol strategy for bronze bug.